2016
DOI: 10.1080/00207543.2015.1134840
|View full text |Cite
|
Sign up to set email alerts
|

Smart box-enabled product–service system for cloud logistics

Abstract: Smart box enabled product-service system for cloud logistics Modern logistics takes significant progress and rapid developments with the prosperity of E-commerce, particularly in China. Typical challenges that logistics industry is facing now are composed by a lack of sharing, standard, cost-effective and environmental package, and efficient optimization method for logistics tasks distribution. As a result, it is difficult to implement green, sustainable logistics services. Three important technologies, Physic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
59
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 101 publications
(60 citation statements)
references
References 31 publications
0
59
0
1
Order By: Relevance
“…Chen studied the benefits of CMfg in the following respects: cost savings, efficiency, additional data analysis capabilities, flexibility, and closer partner relationships . Zhang proposed smart box enabled product service system for cloud logistics based on IoT and cloud computing (CC) . Tao et al.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Chen studied the benefits of CMfg in the following respects: cost savings, efficiency, additional data analysis capabilities, flexibility, and closer partner relationships . Zhang proposed smart box enabled product service system for cloud logistics based on IoT and cloud computing (CC) . Tao et al.…”
Section: Literature Reviewmentioning
confidence: 99%
“…As [36] emphasize logistics' characteristics of physical and non-physical objects and thus, argue for a product service system view on logistics, the method based on extended service blueprinting is suitable. When creating a basic cloud Logistics Service Blueprint (CLSB), which is based on the extended service blueprinting, the concept shown in Figure 3 has to be encapsulated and logistics characteristics have to be taken into account.…”
Section: Cloud Logistics Service Blueprintmentioning
confidence: 99%
“…Sensors are linked in order to retrieve current state parameters of physical resources. Zhang et al [36] emphasize the combined characteristics of logistics of physical and non-physical objects and thus, argue for a product service system view on logistics. (Logistics) services are encapsulated and accessible via XMLbased description and interface.…”
Section: A Systematic Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Leseure et al 17 identified critical and frequent challenges experienced by UK manufacturing companies undergoing a servitization journey to becoming product service system providers. Zhang et al 18 proposed a smart box-enabled product-service system for cloud logistics, in which Physical Internet, product-service system, and cloud computing were developed. It should be noted that Jiang and Zhu 19 has done much research on introducing IPSS idea into manufacturing equipment, such as an IPSS for computer numerical control (CNC) machine tool (mt-iPSS) and cutting tools (ct-iPSS).…”
Section: Brief Reviewmentioning
confidence: 99%